Hindrance to Online Education during Lockdowns: Insights and Measures - Sumitra Pokhrel; Roshan Chhetri (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2021)
This study aims to identify the hindrances to online education students in schools and colleges during the lockdown. The online survey through Google Forms with a structured questionnaire with both restricted and unrestricted responses was designed to identify the hindrance to online education during the third lockdown. Total of 425 responses of students who attend online classes during lockdown from Phuentsholing Higher Secondary, Phuentsholing Middle Secondary, Sonamgang Middle Secondary Schools, and College of Science and Technology in Phuentsholing, Bhutan. The result indicates that socio-economic, technological, and psychological situations hinder effective online teaching and learning. Household chores, large family members, data packages, and poor internet connectivity are other difficulties students face making online education ineffective. Some of the measures to support economically disadvantaged students and provide personal computers/laptops to teachers for preparing and developing teaching-learning materials are suggested. Other recommendations and viable measures based on surveys are suggested to overcome such challenges for students and support providers to make online education effective and focused